APPLICATION OF INCLUSIVE DESIGN TO SCHOOL ACCESSIBILITY AS A FORM OF EQUALITY FOR PEOPLE WITH DISABILITIES - Bahari, Puspita Indah; Musthafa, Rahmat Nur; Arisanti, Sita Aghisna; Harmunisa, Yusvika Ratri (ADBE, 2023)
Education is a basic right of every Indonesian citizen, including those with special needs. The role of the government in creating education equity is necessary to the educational revolution. Thus, Inclusive School is an important educational service as a facility for the students with special needs in receiving education with normal students. The implementation of inclusive schools in Indonesia has not been in line with the proposed concept, especially due to inadequate facilities and infrastructure. In this case, the implementation of inclusive design concepts should be realized by spaces and buildings that can be suitably accessed by everyone. This research contributes to the achievement of Sustainable Development Goals (SDGs), namely Quality Education & Peace, Justice and Strong Institutions, namely providing educational opportunities that are as decent as normal children so that they can maximize their potential. This study aims to identify the concept of accessibility of inclusive school design. This study uses qualitative methods by comparing two precedents, SMPN 2 Sewon and SMPN 15 Yogyakarta, to identify the condition of inclusive schools in Yogyakarta, especially for children with disabilities. There are three variables studied: accessibility, comfort and safety. This study finds that these two schools are disability-friendly because they have implemented the concept of inclusion that is not only achieved by building design, but also supported by the special teachers as well as several other supporting facilities.